Take It Back - Kia Abdullah (London Harper Collins, 2020)
"From author Kia Abdullah, Take It Back is a harrowing and twisting courtroom thriller that keeps you guessing until the last page is turned. One victim. Four accused. Who is telling the truth? Zara Kaleel, one of London's brightest legal minds, shattered the expectations placed on her by her family and forged a brilliant legal career. But her decisions came at a high cost, and now, battling her own demons, she has exchanged her high profile career for a job at a sexual assault center, helping victims who need her the most. Victims like Jodie Wolfe. When Jodie, a sixteen-year-old girl with facial deformities, accuses four boys in her class of an unthinkable crime, the community is torn apart. After all, these four teenage defendants are from hard-working immigrant families and they all have proven alibis. Even Jodie's best friend doesn't believe her. But Zara does--and she is determined to fight for Jodie--to find the truth in the face of public outcry. And as issues of sex, race and social justice collide, the most explosive criminal trial of the year builds to a shocking conclusion"